Visual Field Defect Before and After Endovascular Treatment of Occipital Arteriovenous Malformations. (18th November 2021) - Smajda, Stanislas; Ciccio, Gabriele; Fahed, Robert; Robert, Thomas; Botta, Daniele; Redjem, Hocine; Desilles, Jean-Philippe; Mazighi, Mikael; Zuber, Kevin; Escalard, Simon; Baharvahdat, Humain; Blanc, Raphaël; et al.
Graphical Abstract: